Experimental study of the shear failure of granite based on full-field-strain monitoring using digital image correlation. Issue 2 (October 2021) - Li, Jia Qi; Liang, Peng; Sun, Lin; Yao, Xu Long; Liu, Jun Ling; Li, Zhuang
Abstract: Shear failure is a common failure form of engineering rock mass. As a typical engineering rock mass, granite is widely present in reservoir dams, mine slopes, mine roadways, and other projects in China. Therefore, in this study, the direct shear testing of granite was conducted by taking granite as the research object and using an RLW-3000 shear creep biaxial testing machine. The complete process of shear failure was monitored by using digital image correlation non-contact full-field strain measurement technology, and the spatial evolution of the shear-failure process of granite was assessed by analyzing the main strain nephogram in combination with the main strain–time variation curves. The spatiotemporal evolution of strain during the shear-failure process of granite was studied to reveal the shear-failure mechanism of the material. Results show that the strain nephogram of granite during shear failure could be divided into four stages: uniform strain distribution, strain-localization band generation, strain band expansion, and strain-band expansion acceleration. Strain localization is an important feature of the shear failure of a rock mass; it is characterized by the uneven distribution of strain on the surface of the specimen and the appearance of strain-concentration bands, which indicate the initiation and propagation of macroscopic shear cracks. According to the principal strain–time curve obtained, the principal strain curve exhibits a sharp upward trend when strain localization occurs, and the stress is approximately 76%–79% of the peak stress. The space–time evolution characteristics of the above strain reflect the spatiotemporal variations in the stress field on the surface of the specimen, and the spatial extension of the banded strain-concentration area corresponds to the formation and development of shear failure in the rock. Therefore, the direction of the spatial development of shear microfractures can be predicted by capturing the spatial development of strain-localization bands. The results of this work provide an important theoretical basis and guidance for reservoir dam seepage prevention, highway and mine slope support, and goaf face instability early-warning systems.